Effects of vegetation structure and edge proximity on insect distribution in an arboreal Caatinga area in Brazil - Oliveira, Jefferson Bruno Bretas Souza; Pereira, Bárbara Albuquerque; Silva, Aline Sousa; Bezerra, Isaque Clementino; Araújo, Walter Santos de (Journal of Environmental Analysis and Progress, 2020)
Caatinga is a very important and neglected dry tropical forest biome of Brazil. Recent evidence indicates that anthropogenic threats to Caatinga have grown in recent years, and there are still gaps in the knowledge of how these effects alter biodiversity. In the present study, we evaluated the effects of vegetation structure and edge proximity on the distribution of bioindicator insects (galling insects and ants) in an arboreal Caatinga area under the influence of a monoculture in Brazil. We recorded a total of 10 species and 2,131 specimens of ants and 11 species and 29 individuals of galling insects. Species richness, abundance, and composition of galling insects and ants did not differ between edge and interior plots of the forest. Ant diversity was also not affected by the structural parameters of vegetation (plant abundance, vegetation cover, and vegetation height). On the other hand, the plant abundance positively influenced the richness and the abundance of galling insects in the plots. Our findings suggest that the distribution of ants and galling insects in Caatinga forest edge and interior environments did not differs likely due the opening of the canopy gives the arboreal Caatinga relatively homogeneous climatic characteristics throughout the forest. Already the structure of vegetation positively influences galling insects due to the high degree of dependence that endophagous life-form generates on these insects. Our results show that despite similar responses to the edge effect, ants and galling insects respond differently to vegetation structure, indicating that the structuring of these insect communities is guild-dependent.